Zearalenone and Metabolites in Livers of Turkey Poults and Broiler Chickens Fed with Diets Containing Fusariotoxins - Tardieu, Didier (Toxins (Basel), 2020)
Zearalenone (ZEN) and metabolites were measured in livers of turkeys and broilers fed a control diet free of mycotoxins, a diet that contained 0.5 mg/kg ZEN (ZEN diet), and a diet that contained 0.5, 5, and 20 mg/kg of ZEN, fumonisins, and deoxynivalenol, respectively (ZENDONFB diet). The feed was individually distributed to male Grade Maker turkeys from the 55th to the 70th day of age and to male Ross chickens from the 1st to the 35th day of age, without any signs of toxicity. Together, the free and conjugated forms of ZEN, α- and β-zearalenols (ZOLs), zearalanone (ZAN), and α- and β-zearalanols (ZALs) were measured by UHPLC-MS/MS with [(13)C(18)]-ZEN as an internal standard and immunoaffinity clean-up of samples. ZAN and ZALs were not detected. ZEN and ZOLs were mainly found in their conjugated forms. α-ZOL was the most abundant and was found at a mean concentration of 2.23 and 1.56 ng/g in turkeys and chickens, respectively. Consuming the ZENDONFB diet significantly increased the level of total metabolites in the livers of chickens. Furthermore, this increase was more pronounced for the free forms of α-ZOL than for the conjugated forms. An investigation of the presence of ZEN and metabolites in muscle with the methods validated for the liver failed to reveal any traces of these contaminants in this tissue. These results suggest that concomitant dietary exposure to deoxynivalenol (DON) and fumonisins (FB) may alter the metabolism and persistence of ZEN and its metabolites in the liver.